Optimasisasi Mobile Ad-Hoc Network dengan Algoritma Particle Swarm Optimization - Alon Jala Tirta Segara; Aditya Wijayanto (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
In this digital era the development of technology occurs an evolution in media technology, let's call it new media or people also often call it online media or people are more familiarly called it the internet, this media is certainly familiar to the ears. The delivery of data for communication can be hampered because of the lack of satellites caused by the weather or because of damage to the satellites and delays in the delivery of data that may result in late entry of information. Therefore we want to implement mobile ad-hoc network (manet) and evaluate the results of the manet method by knowing the results of end to end delay and packet delivery ratio Normalized routing load to know the existing. The research method uses simulation method and evaluation of routing model using Network Simulator. Evaluation is prioritized on the use of existing calculated parameters to test the AOMDV protocol and then we use the PSO algorithm to be able to optimize the value of existing calculated parameters. In this study has been done by using 2 scenarios with each scenario has a number of nodes namely 30 and 50 ago with an area of 1000m x 1000m and also data delivery speed of 200/kbps and speed of 200 in each scenario. After doing the simulation and looking at the existing comparison values, we came to a conclusion about the results of the parameter trial above obtained the average value of PDR on nodes 50 95.1 and nodes 30 81.5%, NRL values on nodes 50 51.4% and nodes 30 12.7%. While in optimization value with PSO each parameter occurs in a significant increase in PDR and NRL parameter value while for Avaerage delay value there is a decrease in each simulation value.